Business models on the basis of digital infrastructure data - Schulz, Steve; Trojahn, Sebastian (Advanced Logistic Systems - Theory and Practice, 2024)
The project Ready for Smart City Robots (R4R) is developing strategies for the detailed capture of infrastructural environmental parameters. These are intended to be utilized for autonomous mobility and logistics applications on pedestrian and bicycle paths. The project evaluates the quality and completeness of data for Smart City concepts, using examples from (autonomous) micro-mobility in logistics and transportation. The results encompass the following areas: firstly, the identification of necessary environmental information for environmentally friendly, automated last-mile logistics, along with a continuous data collection method for up-to-date information. Secondly, the examination of various integration scenarios for autonomous delivery services and an autonomous bicycle rental system in rural areas. This includes the development of application scenarios and the scientific support of the prototype construction of the necessary technical prerequisites for the data/sensor boxes. The following outlines the business model potentials for data collection, autonomous micro-mobility, sharing services, and Smart City applications.